-3(6p+3)-2(4-14p)=3(2+3p)

Simple and best practice solution for -3(6p+3)-2(4-14p)=3(2+3p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6p+3)-2(4-14p)=3(2+3p) equation:



-3(6p+3)-2(4-14p)=3(2+3p)
We move all terms to the left:
-3(6p+3)-2(4-14p)-(3(2+3p))=0
We add all the numbers together, and all the variables
-3(6p+3)-2(-14p+4)-(3(3p+2))=0
We multiply parentheses
-18p+28p-(3(3p+2))-9-8=0
We calculate terms in parentheses: -(3(3p+2)), so:
3(3p+2)
We multiply parentheses
9p+6
Back to the equation:
-(9p+6)
We add all the numbers together, and all the variables
10p-(9p+6)-17=0
We get rid of parentheses
10p-9p-6-17=0
We add all the numbers together, and all the variables
p-23=0
We move all terms containing p to the left, all other terms to the right
p=23

See similar equations:

| 3x^-2x=1 | | 8-n/6=10 | | q^2+20q=-4q^2+8400 | | y=1/4×(-4)-3 | | q^2+20q=8400 | | 3x+3x^2=180 | | y=1/4×-4-3 | | 1.7q-5.2-1.4q=-0.7q-4.6 | | 3x+3^2=180 | | 6=z+10/4 | | -28=5w-3w | | 6−x−3=10 | | 3t-5t=11 | | 4x+5-12=3x-2 | | 15x-164=180 | | 8a-10=10 | | -u+102=258 | | 2−5(x+5)=3(x−2)−1 | | -w+212=91 | | (1)/(2)(4z+(1)/(4))=2(z+(1)/(16)) | | 3x²-40x+75=0 | | 9x+4=7x+15 | | -42=-x/9 | | 7p+11=-16-2p | | 2(-3x+1)+3(-2x+1)=13-4(3x+2) | | 3(x-6)+8=13 | | 2x-3=(1/2)x+17 | | 16v=17v+12 | | -3(w-1)=3w+33 | | -5k-29=5-13k | | -r-10=6r+6-5r | | 50+100nn=2 |

Equations solver categories